2014
DOI: 10.1158/1078-0432.ccr-13-2221
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RET Increases the Efficacy of Antiestrogen and Is a Novel Treatment Strategy for Luminal Breast Cancer

Abstract: Purpose Recent findings suggest that combination treatment with anti-estrogen and anti-RET may offer a novel treatment strategy in a subset of breast cancer patients. We investigated the role of RET in potentiating the effects of anti-estrogen response and examined whether RET expression predicted the ability for tyrosine kinase inhibitor (TKI) to affect ERK1/2 activation in primary breast cancer. Experimental Design Growth response, ERK1/2 activation, Ki-67 and TUNEL were assessed in breast cancer cell line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…In the luminal MCF-7 and BT-474 cell lines, transient knockdown of RET reduced in vitro cell proliferation, which was implicated to occur through changes in the MAP kinase pathway, as knockdown of RET led to reduced levels of phosphorylated extracellular-signal-regulated kinases (p-ERK) (12). We compared the effect of knockdown of RET and EGFR alone and in combination.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the luminal MCF-7 and BT-474 cell lines, transient knockdown of RET reduced in vitro cell proliferation, which was implicated to occur through changes in the MAP kinase pathway, as knockdown of RET led to reduced levels of phosphorylated extracellular-signal-regulated kinases (p-ERK) (12). We compared the effect of knockdown of RET and EGFR alone and in combination.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that vandetanib treatment of the luminal MCF-7 and BT-474 cells in vitro reduced cell proliferation (12). However, vandetanib has TKI activity that targets several RTKs including RET and EGFR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an autoregulatory loop is intriguing and has to be taken into consideration for the development of new targeted therapies in BC [45].…”
Section: Discussionmentioning
confidence: 99%